BS EN IEC 61156-13. Multicore and symmetrical pair/quad cables for digital communications. Part 13. Symmetrical single pair cables with transmission characteristics up to 20 MHz. Horizontal floor wiring. Sectional specification (7th May 2021) - British Standards Institution,
No abstract available